2015
DOI: 10.1681/asn.2015040345
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Deceased-Donor Urine Injury Biomarkers and Kidney Transplant Outcomes

Abstract: Assessment of deceased-donor organ quality is integral to transplant allocation practices, but tools to more precisely measure donor kidney injury and better predict outcomes are needed. In this study, we assessed associations between injury biomarkers in deceased-donor urine and the following outcomes: donor AKI (stage 2 or greater), recipient delayed graft function (defined as dialysis in first week post-transplant), and recipient 6-month eGFR. We measured urinary concentrations of microalbumin, neutrophil g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 42 publications
1
89
2
1
Order By: Relevance
“…14,15 Briefly, we collaborated with five organ procurement organizations (OPOs). These OPOs collected donor urine samples as per study protocol at the time of organ procurement between April 2010 and November 2013 from donors whose surrogates had given consent for research.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 Briefly, we collaborated with five organ procurement organizations (OPOs). These OPOs collected donor urine samples as per study protocol at the time of organ procurement between April 2010 and November 2013 from donors whose surrogates had given consent for research.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that increased local production of NGAL by the tubular epithelium of DGF kidneys contributes to the high circulating and urine levels, reflecting the ischemia/reperfusion stress applied to the transplanted kidney before organ withdrawal, during the storage period, and during successive reperfusion. [9][10][11] NGAL is a 25 kDa protein belonging to the lipocalin superfamily. It was initially found in activated neutrophils; however, many other cells, like kidney tubular cells, may produce it in response to various insults.…”
mentioning
confidence: 99%
“…However, failed to predict DGF in the receiver operating characteristic (ROC) analysis. Reese et al (35) also documented the association of donor uNGAL with consequent DGF, but with lower incidence in comparison to the findings of Hollmen et al (34). Furthermore, both uNGAL and uL-FABP were in association with a lower estimated GFR (eGFR) at sixmonths, but only in recipients in absence of DGF.…”
Section: Urine Biomarkersmentioning
confidence: 90%
“…Furthermore, both uNGAL and uL-FABP were in association with a lower estimated GFR (eGFR) at sixmonths, but only in recipients in absence of DGF. Based on these data, the authors concluding that donor urine injury biomarkers procure exiguous value to predict DGF and early allograft function after transplantation (35). Koo et al (36) reconsidered these data with their findings.…”
Section: Urine Biomarkersmentioning
confidence: 99%